Assessment on the climate change impact using CMIP6 - Wan Zunairah, Othman; Nurul Nadrah Aqilah, Tukimat (Institute of Physics, 2023)
The impact of global warming is resulting in flood, land slide, soil erosion and drought that are anticipated to become more intense and frequent. The history record shows that the flood has been occur repeatedly in this study area. The study of future climate needs to be done to a greater extent as a planning for the infrastructure and as mitigation actions on flood based on the future climate. The aims of this study, to ascertain the climate projection by CMIP6 are compatible to be subjected for the future climate and to identify the trend of future climate projection in Kemaman, Terengganu. The comprehensive study of future climate that using CMIP6 that consist of SSPs help in providing a clear explanation of future society's socio-economic appraisal in assessment modelling. The Sen's Slope Test were used to analyze the trend of future climate projection in this study area. In this study, we found out that the trend of future rainfall is increasing with the positive values of Sen's Slope Test. Study shows that the Sen's Slope Test values for eight (8) stations in Kemaman, which is Ban Ho, Hulu Jabor, Rumah Pam Paya Kempian, JPS Kemaman, Klinik Bidan Kg Ibok, SK Kemasek, Jambatan Tebak, and Jambatan Air Putih are 2.381, 1.158, 1.333, 1.252, 2.293, 1.06, 3.113, and 1.961 respectively. The frequency and intensity of forecasting rainfall also increasing compared to the historical data. In conclusion, the proper planning and mitigation action need to be done to minimize the losses that happen due to climate changes impacts.